The Role of a Resident Aesthetic Clinic in Addressing the Trainee Autonomy Gap. (14th November 2019) - Shakir, Sameer; Kozak, Geoffrey M; Nathan, Shelby L; Davis, Harrison; Whitely, Cutler; Broach, Robyn B; Fosnot, Joshua
Abstract: Background: Our institution supports a chief resident aesthetic clinic with the goal of fostering autonomy and preparedness for independent practice in a safe environment. Objectives: The aim of this study was to compare safety profiles and costs for common aesthetic procedures performed in our resident versus attending clinics. Methods: A retrospective review was conducted of all subjects presenting for aesthetic face, breast, and/or abdominal contouring surgery at our institution from 2008 to 2017. Two cohorts were identified: subjects undergoing surgery through the chief resident versus attending clinics. Aesthetic procedures queried included: (1) blepharoplasty, rhinoplasty, or rhytidectomy; (2) augmentation mammaplasty, reduction mammaplasty, or mastopexy; (3) abdominoplasty; and (4) combination. Demographics, perioperative characteristics, costs, and postoperative complications were analyzed. Results: In total, 262 and 238 subjects underwent aesthetic procedures in the resident and attending clinics, respectively. Subjects presenting to the residents were younger ( P < 0.001), lower income ( P < 0.001), and had fewer comorbidities ( P < 0.001). Length of procedure differed between resident and attending cohorts at 181 and 152 minutes, respectively ( P < 0.001), although hospital costs were not significantly increased. Total costs were higher in the attending cohort independent of aesthetic procedure ( P < 0.001). Hospital readmissions ( P < 0.05) and cosmetic revisions ( P < 0.002) were more likely to occur in the attending physician cohort. Postoperative complications ( P < 0.50) and reoperative rates ( P < 0.39) were not significantly different. Conclusions: The resident aesthetic clinic provides a mechanism for increased autonomy and decision-making, while maintaining patient safety in commonly performed cosmetic procedures.